A kind of high polymer environmentally friendly recycled concrete and preparation method thereof
By adding polymers and other blends to the recycled concrete, a grid structure of polymers and cement is formed, which solves the problems of insufficient strength, high chloride ion content and environmental impact of recycled concrete, and achieves high-strength, high durability and environmental protection recycled concrete.
Patent Information
- Application Number
- CN202310361936.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-07
AI Technical Summary
Recycled concrete has shortcomings in strength, durability, environmental impact and construction convenience, including insufficient strength, high chloride ion content, carbon dioxide production, vertical warping and deformation.
Using a technical solution for polymer environmentally friendly recycled concrete, by adding cement, fly ash, silicate particles, polymer emulsion, glass fiber and water reducer, combined with scientific proportioning and treatment methods, a grid of polymers and cement penetrates each other is formed to improve the strength and durability of concrete, and reduce the chloride ion content through screening and soaking.
It significantly improves the strength, durability and crack resistance of recycled concrete, reduces chloride ion content and carbon dioxide emissions, reduces resource waste and environmental pollution, and is easy to construct and has low cost.
Smart Images

Figure BDA0004165373810000071 
Figure BDA0004165373810000081 
Figure BDA0004165373810000082
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, and in particular to a polymer environmentally friendly recycled concrete. Background Art
[0002] Recycled concrete is concrete made from recycled and reused waste concrete, and its use can reduce environmental pollution and the consumption of natural resources. However, recycled concrete may also encounter the following problems: 1. Insufficient strength: The quality of raw materials such as crushed stone and sand in recycled concrete may vary, resulting in its strength being inferior to that of fresh concrete, which poses a challenge to some projects that require high strength. 2. High chloride ion content: Recycled and reused waste concrete may contain high concentrations of chloride ions, which can cause steel corrosion and cracking on the concrete surface, reducing the durability of concrete structures. 3. Carbon dioxide generation: The preparation process of recycled concrete requires operations such as rolling and washing, which may generate a large amount of carbon dioxide emissions, further exacerbating environmental pollution. 4. Vertical warping: Due to the different sizes of particles in recycled concrete, the concrete may warp vertically when drying, which will cause inconvenience in construction. 5. Deformation: Since the raw materials of recycled concrete are not screened, the particle size distribution range is large. It may cause deformation, affecting the performance and service life of concrete. Appropriate measures need to be taken to address these issues, such as improving the quality of recycled concrete by adding an appropriate amount of fresh concrete and strengthening quality control, and ensuring its safe and reliable use in projects. Summary of the invention
[0003] In view of this, the present invention proposes a polymer environmentally friendly recycled concrete to solve the above problems.
[0004] The technical solution of the present invention is achieved as follows: a polymer environmentally friendly recycled concrete: comprising the following raw materials in parts by weight: 500-800 parts of recycled concrete, 200-500 parts of cement, 25-50 parts of fly ash, 18-28 parts of silicate particles, 58-89 parts of polymer emulsion, 15-35 parts of glass fiber, and 13-30 parts of water reducing agent. Fly ash and silicate particles can effectively absorb chloride ions and reduce the content in concrete.
[0005] Furthermore, the polymer environmentally friendly recycled concrete comprises the following raw materials in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 70 parts of polymer emulsion, 25 parts of glass fiber, and 22 parts of water reducing agent.
[0006] Furthermore, the silicate particles have a particle size of 40-48 μm.
[0007] Furthermore, the polymer emulsion is methyl methacrylate, acrylic acid, styrene and polyvinyl alcohol in a volume ratio of 3-6:2-8:1-4:0.3-0.8, which can improve the bonding strength and anti-seepage performance of concrete, wherein the polyvinyl alcohol can prevent the polymer emulsion from hydrolyzing or precipitating during preparation and use.
[0008] Furthermore, the method for preparing the polymer environmentally friendly recycled concrete comprises the following steps:
[0009] S1. Screening of raw materials: Select high-quality recycled bricks and concrete for cleaning and screening, remove dirt and impurities, and prevent these impurities from bringing in harmful substances such as chloride ions. Then soak them in salt water to release most of the water containing chloride ions in a short time, reduce the chloride ion content in the concrete, take them out, drain them, and crush them to obtain recycled concrete;
[0010] S2. Adding admixtures: mixing recycled concrete, cement, fly ash and silicate particles, and stirring evenly to obtain a mixture A;
[0011] S3, adding polymer: putting the above mixture A and polymer emulsion into a mixer, adding water into the mixer and stirring evenly to improve the strength, durability and toughness of the concrete, to obtain mixture B;
[0012] S4, adding additives: adding glass fiber and water reducing agent into the mixer, and continuing to stir until the mixture B and the additives are evenly mixed to obtain a slurry-like recycled concrete mixture;
[0013] S5. Casting and molding: pour the uniformly mixed slurry recycled concrete mixture into the mold, and then vibrate and compact it with a vibrator to achieve the required density and shape;
[0014] S6. Curing and hardening: After pouring, it should be cured and hardened in time to achieve the strength and durability required by the design.
[0015] Furthermore, the crushed particle size of the S1 is less than 40 μm.
[0016] Furthermore, the salt water concentration of S1 is 3.1-5.9%, and the soaking time is 20-60 minutes.
[0017] Furthermore, the stirring rate of S2 is 400-600 rpm, and the stirring time is 30-40 min.
[0018] Furthermore, the mass volume ratio of the S3 mixture A to water is 9-12:1 g / mL.
[0019] Furthermore, the stirring rates of S3 and S4 are both 600-800 rpm, the stirring time of S3 is 60-90 min, and the stirring time of S4 is 30-50 min.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The polymer environmentally friendly recycled concrete of the present invention is an environmentally friendly building material that utilizes waste concrete for recycling and reuse. It uses a high molecular polymer as a concrete additive, which is immersed in the porous concrete in the form of a monomer, and then the monomer is polymerized on the concrete interface, and then the polymerization process is extended to the center. The high molecular polymer infiltrates into the monomers in the gaps and polymerizes to form a grid in which the polymer and cement penetrate each other, so as to improve the strength and durability of the concrete. By selecting high molecular emulsion raw materials and scientifically proportioning them, their better performance strength can be synergistically exerted, and adding polyvinyl alcohol as a stabilizer can prevent the high molecular emulsion from being hydrolyzed or precipitated during the preparation and use process, thereby enhancing the mechanical properties of the concrete.
[0022] The present invention can improve the strength and stability of concrete by adding admixtures such as cement, fly ash, silicate particles, etc., and the addition of glass fiber increases the durability and crack resistance of concrete. The water-reducing agent can reduce the water-cement ratio of concrete and improve the fluidity and slump of concrete. The prepared polymer environmentally friendly recycled concrete has good environmental protection, adopts recycled and reused old concrete as raw material, and can effectively reduce waste of resources and environmental pollution. The addition of polymer can improve the strength and durability of concrete, making it more durable, strong, compression-resistant and crack-resistant. Due to the recycling and reuse of waste concrete, the preparation cost of the polymer environmentally friendly recycled concrete is relatively low, which can achieve the purpose of saving resources and reducing construction costs. The construction method of the polymer environmentally friendly recycled concrete is basically the same as that of traditional concrete, does not require special technology and equipment, and is convenient to construct.
[0023] The polymer environmentally friendly recycled concrete of the present invention is an environmentally friendly, high-strength, and highly durable new building material, and can be used for research in various concrete structural projects, such as buildings, roads and bridges, underground projects, and the like. DETAILED DESCRIPTION
[0024] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0025] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0026] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0027] Example 1
[0028] A polymer environmentally friendly recycled concrete: the following raw materials are weighed in parts by weight: 500 parts of recycled concrete, 200 parts of cement, 25 parts of fly ash, 18 parts of silicate particles, 58 parts of polymer emulsion, 15 parts of glass fiber, and 13 parts of water reducing agent. The silicate particles have a particle size of 40 μm, and the polymer emulsion is methyl methacrylate, acrylic acid, styrene and polyvinyl alcohol in a volume ratio of 3:2:1:0.3.
[0029] Example 2
[0030] A polymer environmentally friendly recycled concrete: the following raw materials are weighed in parts by weight: 800 parts of recycled concrete, 500 parts of cement, 50 parts of fly ash, 28 parts of silicate particles, 89 parts of polymer emulsion, 35 parts of glass fiber, and 30 parts of water reducing agent. The silicate particles have a particle size of 48 μm, and the polymer emulsion is methyl methacrylate, acrylic acid, styrene, and polyvinyl alcohol in a volume ratio of 6:8:4:0.8.
[0031] Example 3
[0032] A polymer environmentally friendly recycled concrete: the following raw materials are weighed in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 70 parts of polymer emulsion, 25 parts of glass fiber, and 22 parts of water reducing agent. The silicate particles have a particle size of 44 μm, and the polymer emulsion is methyl methacrylate, acrylic acid, styrene, and polyvinyl alcohol in a volume ratio of 5:5:3:0.5.
[0033] The above examples 1-3 adopt the following preparation method:
[0034] S1. Screening raw materials: Select high-quality recycled bricks and concrete, wash and screen them, remove the dirt and impurities, soak them in salt water with a concentration of 4.2% for 40 minutes, take them out, drain them, and crush them into particles with a size less than 40 μm to obtain recycled concrete;
[0035] S2. Add admixture: Mix the recycled concrete, cement, fly ash and silicate particles at a stirring rate of 500 rpm for 35 min to obtain a mixture A;
[0036] S3, adding polymer: putting the above mixture A and polymer emulsion into a mixer, adding water into the mixer and stirring evenly, the stirring rate is 700 rpm, the stirring time is 80 min, the mass volume ratio of mixture A to water is g / mL 10:1, so as to improve the strength, durability and toughness of concrete, and obtain mixture B;
[0037] S4, adding additives: adding glass fiber and water reducing agent into the mixer, and continuing stirring at a stirring rate of 700 rpm for 40 min until the mixture B and the additives are evenly mixed to obtain a slurry-like recycled concrete mixture;
[0038] S5. Casting and molding: pour the uniformly mixed slurry recycled concrete mixture into the mold, and then vibrate and compact it with a vibrator to achieve the required density and shape;
[0039] S6. Curing and hardening: After pouring, it should be cured and hardened in time to achieve the strength and durability required by the design.
[0040] Example 4
[0041] A polymer environmentally friendly recycled concrete: the following raw materials are weighed in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 70 parts of polymer emulsion, 25 parts of glass fiber, and 22 parts of water reducing agent. The silicate particles have a particle size of 44 μm, and the polymer emulsion is methyl methacrylate, acrylic acid, styrene, and polyvinyl alcohol in a volume ratio of 5:5:3:0.5.
[0042] S1. Screening raw materials: Select high-quality recycled bricks and concrete, wash and screen them, remove the dirt and impurities, soak them in salt water with a concentration of 3.1% for 20 minutes, take them out, drain them, and crush them into particles with a size less than 40 μm to obtain recycled concrete;
[0043] S2. Add admixture: Mix the recycled concrete, cement, fly ash and silicate particles at a stirring rate of 400 rpm for 30 min to obtain a mixture A;
[0044] S3, adding polymer: putting the above-mentioned mixed material A and polymer emulsion into a blender, adding water into the blender and stirring evenly, the stirring speed is 600 rpm, the stirring time is 60 min, the mass volume ratio of mixed material A to water is 9:1 g / mL, and mixed material B is obtained;
[0045] S4, adding additives: adding glass fiber and water reducing agent into the mixer, and continuing stirring at a stirring rate of 600 rpm for 30 min until the mixture B and the additives are evenly mixed to obtain a slurry-like recycled concrete mixture;
[0046] S5. Casting and molding: pour the uniformly mixed slurry recycled concrete mixture into the mold, and then vibrate and compact it with a vibrator to achieve the required density and shape;
[0047] S6. Curing and hardening: After pouring, it should be cured and hardened in time to achieve the strength and durability required by the design.
[0048] Example 5
[0049] A polymer environmentally friendly recycled concrete: the following raw materials are weighed in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 70 parts of polymer emulsion, 25 parts of glass fiber, and 22 parts of water reducing agent. The silicate particles have a particle size of 44 μm, and the polymer emulsion is methyl methacrylate, acrylic acid, styrene, and polyvinyl alcohol in a volume ratio of 5:5:3:0.5.
[0050] S1. Screening raw materials: Select high-quality recycled bricks and concrete for cleaning and screening to remove dirt and impurities, and then soak them in salt water with a concentration of 5.9% for 60 minutes, take them out, drain them, and crush them to a particle size of less than 40 μm to obtain recycled concrete;
[0051] S2. Add admixture: Mix the recycled concrete, cement, fly ash and silicate particles at a stirring rate of 600 rpm for 340 min to obtain a mixture A;
[0052] S3, adding polymer: putting the above-mentioned mixed material A and polymer emulsion into a blender, adding water into the blender and stirring evenly, the stirring speed is 800 rpm, the stirring time is 90 min, the mass volume ratio of mixed material A to water is 12:1 g / mL, and mixed material B is obtained;
[0053] S4, adding additives: adding glass fiber and water reducing agent into the mixer, and continuing stirring at a stirring rate of 800 rpm for 50 min until the mixture B and the additives are evenly mixed to obtain a slurry-like recycled concrete mixture;
[0054] S5. Casting and molding: pour the uniformly mixed slurry recycled concrete mixture into the mold, and then vibrate and compact it with a vibrator to achieve the required density and shape;
[0055] S6. Curing and hardening: After pouring, it should be cured and hardened in time to achieve the strength and durability required by the design.
[0056] Comparative Example 1
[0057] The difference between this comparative example and Example 3 is that the polymer environmentally friendly recycled concrete weighs the following raw materials in parts by weight: 400 parts of recycled concrete, 700 parts of cement, 20 parts of fly ash, 35 parts of silicate particles, 40 parts of polymer emulsion, 10 parts of glass fiber, and 10 parts of water reducer. The particle size of the silicate particles is 44 μm, and the polymer emulsion is methyl methacrylate, acrylic acid, styrene and polyvinyl alcohol in a volume ratio of 5:5:3:0.5.
[0058] Comparative Example 2
[0059] The difference between this comparative example and Example 3 is that the polymer emulsion is methyl methacrylate, acrylic acid, styrene and polyvinyl alcohol in a volume ratio of 1:1:3:0.8. Specifically, the following raw materials are weighed in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 70 parts of polymer emulsion, 25 parts of glass fiber, and 22 parts of water reducing agent. The particle size of the silicate particles is 44 μm. The polymer emulsion is methyl methacrylate, acrylic acid, styrene and polyvinyl alcohol in a volume ratio of 1:1:3:0.8.
[0060] Comparative Example 3
[0061] The difference between this comparative example and Example 3 is that the polymer emulsion raw material does not contain polyvinyl alcohol. Specifically, the following raw materials are weighed in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 70 parts of polymer emulsion, 25 parts of glass fiber, and 22 parts of water reducing agent. The silicate particles have a particle size of 44 μm, and the polymer emulsion is methyl methacrylate, acrylic acid, and styrene in a volume ratio of 5:5:3.
[0062] Comparative Example 4
[0063] The difference between this comparative example and Example 3 is that the polymer environmentally friendly recycled concrete raw material does not contain polymer emulsion. Specifically, the following raw materials are weighed in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 25 parts of glass fiber, and 22 parts of water reducing agent, and the particle size of the silicate particles is 44 μm.
[0064] Test Example 1
[0065] The concrete prepared in the above Examples 1-5 and Comparative Examples 1-3 was used as a test sample to test the compressive strength and splitting tensile strength. When the pressure was 50 MPa, it was observed whether cracks appeared on the surface of each group of samples, and the length of the cracks was recorded. The test sample was a cubic standard specimen of 10 cm×10 cm×10 cm. The compressive strength and splitting compressive strength were tested in accordance with GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The results are as follows:
[0066]
[0067]
[0068] The compressive strength and splitting tensile strength of the recycled concrete prepared by the present invention are higher than those of ordinary concrete, and no cracks are generated under pressure. The embodiment group is compared with the comparative example 1, which shows that the recycled concrete has significantly improved cracking strength under appropriate proportions; the embodiment group is compared with the comparative example 2, and the strength of the recycled concrete is improved by targeting the ratio of the polymer emulsions; the embodiment group is compared with the comparative example 3, and the addition of polyvinyl alcohol can prevent the polymer emulsion from being hydrolyzed or precipitated during the preparation and use process, thereby further improving the compressive strength and splitting tensile strength of the recycled concrete, among which the effect of the embodiment 3 is the best.
[0069] Test Example 2
[0070] A comparative example 4 is provided, which differs from example 3 in that the recycled concrete is not immersed in salt water.
[0071] Test: The chloride ion content in the recycled concrete test block of 10cm×10cm×10cm was measured according to GB / T4902-2012. The results are as follows:
[0072]
[0073] In terms of raw material processing, soaking the recycled concrete in salt water can reduce the chloride ion content in the recycled concrete. The chloride ion content is measured to be in line with the requirements of the Chinese standard "Technical Code for Ordinary Concrete" (GB 5008-2013).
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A polymer environmentally friendly recycled concrete, characterized by: The invention comprises the following raw materials in parts by weight: 500-800 parts of recycled concrete, 200-500 parts of cement, 25-50 parts of fly ash, 18-28 parts of silicate particles, 58-89 parts of polymer emulsion, 15-35 parts of glass fiber and 13-30 parts of water reducing agent; The silicate particles have a particle size of 40-48 μm; The polymer emulsion is methyl methacrylate, acrylic acid, styrene and polyvinyl alcohol in a volume ratio of 3-6:2-8:1-4:0.3-0.
8.
2. The polymer environmentally friendly recycled concrete according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 700 parts of recycled concrete, 300 parts of cement, 35 parts of fly ash, 23 parts of silicate particles, 70 parts of polymer emulsion, 25 parts of glass fiber and 22 parts of water reducing agent.
3. The method for preparing the polymer environmentally friendly recycled concrete according to any one of claims 1 or 2, characterized in that: The following steps are involved: S1. Screening of raw materials: Select high-quality recycled bricks and concrete for cleaning and screening to remove dirt and impurities, then soak them in salt water, take them out, drain them, and crush them to obtain recycled concrete; S2. Adding admixtures: mixing recycled concrete, cement, fly ash and silicate particles, and stirring evenly to obtain a mixture A; S3, adding polymer: putting the above mixture A and polymer emulsion into a mixer, adding water into the mixer and stirring evenly to improve the strength, durability and toughness of the concrete, and obtaining mixture B; S4, adding additives: adding glass fiber and water reducing agent into the mixer, and continuing to stir until the mixture B and the additives are evenly mixed to obtain a slurry-like recycled concrete mixture; S5. Casting and molding: pour the uniformly mixed slurry recycled concrete mixture into the mold, and then vibrate and compact it with a vibrator to achieve the required density and shape; S6. Curing and hardening: After pouring, it should be cured and hardened in time to achieve the strength and durability required by the design.
4. The method for preparing the polymer environmentally friendly recycled concrete according to claim 3, characterized in that: The salt water concentration in step S1 is 3.1-5.9%, and the soaking time is 20-60 minutes.
5. The method for preparing the polymer environmentally friendly recycled concrete according to claim 3, characterized in that: The stirring rate of step S2 is 400-600 rpm, and the stirring time is 30-40 min.
6. The method for preparing the polymer environmentally friendly recycled concrete according to claim 3, characterized in that: The mass volume ratio of the mixed material A and water in step S3 is 9-12:1 in g / mL.
7. The method for preparing the polymer environmentally friendly recycled concrete according to claim 3, characterized in that: The stirring rate in steps S3 and S4 is 600-800 rpm, the stirring time in step S3 is 60-90 min, and the stirring time in step S4 is 30-50 min.
Citation Information
Patent Citations
Fiber-reinforced recycled aggregate pervious concrete
CN114804763A